Awakening the control of the ankle dorsiflexors in the post-stroke hemiplegic subject to improve walking activity and social participation: the WAKE (Walking Ankle isoKinetic Exercise) randomised, controlled trial - Ferry, Béatrice; Compagnat, Maxence; Yonneau, Jules; Bensoussan, Laurent; Moucheboeuf, Geoffroy; Muller, François; Laborde, Bertrand; Jossart, Anne; David, Romain; Magne, Julien; Marais, Loïc; Daviet, Jean-Christophe (Current controlled trials in cardiovascular medicine, 2022)
Background Stroke is the leading cause of acquired disability in France. While 90% of patients recover the ability to walk, it is often limited with a steady speed of approximately 0.7 m/s. This limitation of walking activity is partly related to a decrease in strength associated with more or less significant spasticity. In particular, it seems that the strength of the dorsiflexor muscles is directly related to walking speed. We hypothesise that a protocol based on gestural repetition targeted at the ankle during the subacute phase potentiates the recovery of motor control, improving walking activity, and participates in recovering better social participation. Methods An estimated total of 60 patients with subacute stroke will be recruited to participate in this multicentre, interventional, prospective, randomised controlled trial. All participants will benefit from conventional rehabilitation. In addition, the experimental group will take part in an ankle isokinetic rehabilitation programme for 6 weeks (at least 25 sessions). The control group will receive the same duration of conventional rehabilitation. The primary outcome measure will be a 10-m walking speed at post-intervention. Secondary outcomes will include social participation, walking spatio-temporal parameters, and dorsiflexor strength. Outcome measurements will be taken at baseline, immediately after treatment (6 weeks), then at 6 months and 1 year of follow-up. Discussion This study aims to provide scientific evidence that a protocol based on an early over-solicitation of the ankle dorsiflexor muscles to promote their "awakening" can serve to achieve a more effective walking activity, which in turn encourages social participation following discharge from the hospital. This protocol should also help optimise physical medicine and rehabilitation practices: the more systematic use of the isokinetic dynamometer as a technique associated with, and integrated into the conventional rehabilitation protocol would allow an objective evaluation of the rehabilitation benefits and should increase the rehabilitation gain in central nervous system disorders. Trial registration Limoges University Hospital is the sponsor of this research (Unique Protocol ID: 87RI18_0010) This research is supported by the French Ministry of Health (PHRC 2020-A03328-31) and is conducted with the support of DGOS (PHRC interregional - GIRCI SOHO). The study protocol was approved by the French Human Subjects Protection Review Board (Comité de Protection des Personnes Nord-Ouest III) on February 23, 2021. The trial was registered in the ClinicalTrials.gov registry (NCT04800601) on March 16, 2021. Keywords: Stroke, Rehabilitation, Ankle, Gait, Isokinetic, Sub-acute, Social participation